1989
DOI: 10.1007/bf00257543
|View full text |Cite
|
Sign up to set email alerts
|

The two-component stomach: effects of meal particle size on fundal and antral emptying

Abstract: Using a dual-headed gamma camera and a standardized egg test meal labeled with 99mTc-sulfur colloid, the quantitative emptying of the total, proximal and distal stomach in five normal subjects was characterized. The same egg meal was given to the volunteers in 3 different forms: homogenized, and as 2.5 mm and 5.0 mm cubes on 3 separate occasions for a total of 15 studies. For the total stomach emptying, the lag phase and half emptying time (T1/2) obtained using a power exponential model were significantly shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
6

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 22 publications
1
52
0
6
Order By: Relevance
“…Solids and liquids were shown to empty at a similar rate from the stomach if they have comparable macronutrient composition (31). A characteristic lag phase precedes solid emptying, in which they are churned to smaller particle size by propulsive stomach contractions (41). This lag phase seems not to have a major impact on blood glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Solids and liquids were shown to empty at a similar rate from the stomach if they have comparable macronutrient composition (31). A characteristic lag phase precedes solid emptying, in which they are churned to smaller particle size by propulsive stomach contractions (41). This lag phase seems not to have a major impact on blood glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The emptying characteristics of a tenacious semisolid meal resemble those of a solid one. Semisolid meals are not influenced by mastication [2]. Because trituration is not necessary, their propulsion usually starts immediately after ingestion or after a very short lag period.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed the presence of an early lag (trituration) phase for solids followed by a phase during which the stomach empties solids at a characteristic rate (56)(57)(58). To completely characterize these phases of GE, it is best to fit the data to a mathematic function known as a modified power exponential (32), given by…”
Section: Lag Phase Analysismentioning
confidence: 99%